Expression of a glycosylated GFP as a bivalent reporter in exocytosis - Paris, Nadine; Saint-Jean, Bruno; Faraco, Marianna; Krzeszowiec, Weronika; Dalessandro, Giuseppe; Neuhaus, Jean-Marc; Di Sansebastiano, Gian Pietro (My University, 2010)
The complex-type N-linked glycans of plants differ markedly in structure from those of animals. Like those of insects and mollusks they lack terminal sialic acid(s) and may contain an α-(1,3)-fucose (Fuc) linked to the proximal GlcNAc residue and/or a β-(1,2)-xylose (Xyl) residue attached to the proximal mannose (Man) of the glycan core. N-glycosylated GFPs were used in previous studies showing their effective use to report on membrane traffic between the ER and the Golgi apparatus in plant cells. In all these cases glycosylated tags were added at the GFP termini. Because of the position of the tag and depending on the sorting and accumulation site of these modified GFP, there is always a risk of processing and degradation, and this protein design cannot be considered ideal. Here, we describe the development of three different GFPs in which the glycosylation site is internally localized at positions 80, 133, or 172 in the internal sequence. The best glycosylation site was at position 133. This glycosylated GFPgl133 appears to be protected from undesired processing of the glycosylation site and represents a bivalent reporter for biochemical and microscopic studies. After experimental validation, we can conclude that amino acid 133 is an effective glycosylation site and that the GFPgl133 is a powerful tool for in vivo investigations in plant cell biology.
Keywords: GFP; Glycosylation; Protoplast; Secretion